2018
DOI: 10.1016/j.scr.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an induced pluripotent stem cell (iPSC) line from a 40-year-old patient with the A8344G mutation of mitochondrial DNA and MERRF (myoclonic epilepsy with ragged red fibers) syndrome

Abstract: Mitochondrial defects are associated with clinical manifestations from common diseases to rare genetic disorders. Myoclonus epilepsy associated with ragged-red fibers (MERRF) syndrome results from an A to G transition at nucleotide position 8344 in the tRNA gene of mitochondrial DNA (mtDNA) and is characterized by myoclonus, myopathy and severe neurological symptoms. In this study, Sendai reprogramming method was used to generate an iPS cell line carrying the A8344G mutation of mtDNA from a MERRF patient. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The 6 lines of human iPSCs used in this study were generated from the skin fibroblasts established from 3 patients harboring the MERRF syndrome-specific m.8344A > G mutation. Among them, two patients are the members of a Taiwanese MERRF family, a 15-year-old girl (M1-iPSCs) and her 13-year-old sister (M2-iPSCs), and the third patient is a 25-year-old female (M3-iPSCs) as described previously [ 12 , 14 , 16 ]. M1 patient had poor learning ability in childhood and developed myoclonic epilepsy at 12 years of age, and exhibited severe clinical symptoms, including unsteady gait with tremor, intermittent myoclonus and polyneuropathy [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 6 lines of human iPSCs used in this study were generated from the skin fibroblasts established from 3 patients harboring the MERRF syndrome-specific m.8344A > G mutation. Among them, two patients are the members of a Taiwanese MERRF family, a 15-year-old girl (M1-iPSCs) and her 13-year-old sister (M2-iPSCs), and the third patient is a 25-year-old female (M3-iPSCs) as described previously [ 12 , 14 , 16 ]. M1 patient had poor learning ability in childhood and developed myoclonic epilepsy at 12 years of age, and exhibited severe clinical symptoms, including unsteady gait with tremor, intermittent myoclonus and polyneuropathy [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among all iPSCs lines, M1-iPSC sublines (M1 Low and M1 High iPSCs) and M2-iPSCs (M2 High iPSCs) were generated at Taipei Veterans General Hospital and have been used for the studies reported previously [ 12 ]. M3-iPSCs sublines (M3 Low and M3 Med iPSCs) were generated from another MERRF patient in collaboration with Prof. Patrick C. H. Hsieh at the Institute of Biomedical Sciences, Academia Sinica supported by Taiwan Human Disease iPSC Service Consortium [ 14 ]. Prof. Y. C. Hsu at Mackay Medical College kindly provided us the normal iPSCs (IBMS-iPSC-02-07), which were generated from the peripheral blood of a healthy 22-year-old Asian male volunteer and are commercially available from the Food Industry Research and Development Institute, Hsinchu, Taiwan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were found to exhibit characteristic human pluripotent stem cell morphology (Figure 1A). Moreover, they were positive for key markers that are typically screened for to validate pluripotency—Nanog, Sox2, SSEA4, Tra‐1‐60, and Oct‐4, 28–30 thus confirming their identity (Figure 1B–F, respectively).…”
Section: Resultsmentioning
confidence: 65%